Implementation of pumped hydro/photovoltaic systems in mining-degraded areas: a case study in Quadrilátero Ferrífero, Minas Gerais, Brazil - Guimarães, Alberto de Almeida Bossi; Bastos, Adriano Silva; Viana, Edna Maria de Faria; Mendes, Victor Flores; Martinez, Carlos Barreira (International Journal of Renewable Energy Development, 2024)
This work presents a proposal for the transformation of mining-degraded areas into renewable energy installations, converting deactivated mine pits, in the Quadrilátero Ferrífero (QF) region in state of Minas Gerais (MG), Brazil, into reservoirs for Pumped Storage Hydropower (PSH). Additionally, it proposes the alteration of adjacent areas impacted by mining extraction process, through their conversion into Photovoltaic Power Plants (PV). This measure has the potential to turn mining liabilities into sources of energy with lower environmental impact and sustainability for society. This process allows energy to be stored in the form of hydraulic batteries, which can mitigate the effects of intermittency of photovoltaic generation in the electrical grid. The presented methodology involves mapping deactivated mines, calculating the energy potential of the coupled PSH and PV systems, and conducting an economic feasibility study for PSH implementation. The work includes a case study discussing potential local environmental impacts and the energy potentials of this solution. The case study resulted in identifying a suitable pair of mine pits for a PSH in the QF, capable of supplying the electrical grid with approximately 234.3 MW, with the generated energy cost ranging between U$112.26/MWh to U$167.22/MWh. It is concluded that utilizing inactive mines as PSH reservoirs and installing PV in adjacent mining-degraded areas are innovative and technologically feasible strategies. Economically, their implementation will depend on the market price of energy.